EFEKTIFITAS PELATIHAN KOMUNIKASI SBAR PADA PERAWAT DALAM MENCEGAH KESALAHAN PEMBERIAN OBAT DI RUANG ELANG RUMAH SAKIT JIWA DR. SOEHARTO HEERDJAN - Zihan Evrianti Susanto (2023)
One of the things that can be done to prevent patient safety incidents, especially drug administration errors, is to implement effective communication. One of the effective communications that is often used to prevent patient safety incidents is SBAR effective communication. This communication has been widely used but in practice it does not pay much attention to the mention of drugs which can potentially cause drug administration errors. So there is a need for SBAR communication training for nurses. The purpose of implementing evidence based practice in the form of SBAR communication training is to increase the knowledge, understanding and skills of nurses in implementing SBAR communication to prevent medication administration errors. The application of communication training was given to 13 nurses in the Eagle Room of RSJ Dr. Suharto Heerjan. This training is carried out using lecture, discussion and simulation or roleplay methods. The results of implementing the SBAR communication training showed that there was an increase in nurses' knowledge from 6.5 (50%) to 11.5 (88.46%). Based on the comparison of the pretest and posttest values, there is an average increase in knowledge of 38.46%. It can be concluded that SBAR communication training is able to increase nurses' knowledge of SBAR communication. It is necessary to monitor and evaluate procedures related to S-BAR communication at work sites. Hospital management is expected to provide S-BAR communication training to health workers on a regular basis.